(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Government of Karnataka has traditionally given high priority to public housing The State’s allocation for the housing sector is being increased over the years along with formulation of enabling policies and guidelines. It is also one of the few states which have its own housing programmes for the Economically Weaker Sections (EWS) both in rural and urban areas apart from the centrally sponsored housing schemes for EWS. In addition, the Karnataka Housing Board (KHB) provides to housing needs of low income, middle income and high income groups. The Karnataka Slum Development Board (KSDB) is responsible for improvement of slums and resettlement of slum dwellers. Human beings are social animal to live in the society with dignity. Pucca house is required to every citizen of the society. Therefore, Housing is most essential requirement. Adequate shelter for fundamental pre-requisite for a healthy living in any society. To provide housing to all houseless families in the State, Karnataka government has introduced various schemes. With this reason the present paper attempts to know about various housing schemes implemented in Karnataka, entitled “An Economic Analysis of Rural Housing Schemes in Karnataka State”. This study is based on secondary data. Secondary data has been collected from various research papers, magazines, articles, various journals and is also based on the published, unpublished and electronic referred sources. Finally present study has intended to offer suitable suggestions according to finding which are found during study.